الخطاب الديني المعتدل عند الإمام علي(ع) وأثره في الوحدة الإسلامية - الجراح خولة مهدي شاكر (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
It is absurd for anyone to try to deny what happened in long historical periods of human disasters and bloody events that left human society with devastation, devastation, and bloodshed as a result of considering the uneven and differing ideologically and religiously deserving of torment. The pages of history are filled with the infliction of the harshest punishments and the harshest torments on people who had no sin other than differences in opinion and belief, and now there is not much different from the past in the presence of such conflicts and strife from the farthest corners of the world, and the ideological or intellectual conflict is something that cannot be confined to a religion or religion. One doctrine over another what the research aims to achieve is to demonstrate the necessity of recognizing the existence of others who differ with us in opinion, vision, religion, and belief, and to ensure the impossibility of eradicating sectarian and religious pluralism through the practice of cancellation and deletion against it.